Effect of environmental tax reform on corporate green technology innovation - Zhang, Chuan; Zou, Cai Feng; Luo, Wenbo; Liao, Lamei (Frontiers in Environmental Science, 2022)
China has recently taken several measures to counter the environmental pollution caused by the crude model of past economic development. Among them, taxation has proved especially efficient. We take the Environmental Protection Tax Law, implemented on 1 January 2018, as a quasi-natural experiment to study the effect of environmental protection tax reform on corporate green technology innovation. We analyze data on Shanghai and Shenzhen A-share listed companies for 2013–2020. We find that raising the tax levy significantly promotes green innovation among enterprises. The promotion effect is more significant in state-owned enterprises, heavily polluting enterprises, and the eastern region. The findings of the full sample and subsample still hold after replacing the explanatory variables for stability testing. The effects vary significantly based on property rights, geography, and level of industry pollution. Nevertheless, environmental tax reform is an effective initiative toward environmental protection, even if the complexity of China’s economic environment reveals some variation in the effects of this policy reform. We make suggestions to address these differences for future studies.